Multiplex polymerase chain reaction (PCR) assays for the detection of Enterobacteriaceae in clinical samples - Anbazhagan, D.; Kathirvalu, G.G.; Mansor, M.; Yan, G.O.S.; Yusof, M.Y.; Sekaran, S.D. (2010)
The accurate and rapid identification of bacteria in the enteric tract is necessary for early treatment. In this study, we describeD a novel system which consists of a multiplex polymerase chain reaction (PCR) to simultaneously identify a group of six Enterobacteriaceae members including Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Citrobacter spp., Enterobacter cloacae and Salmonella typhi. Genus and species specific primers were designed for this group of pathogens and conventional multiplex PCR and SYBR green based real time PCR assays were performed to detect these pathogens. All the samples were analysed with a eubacterial real-time PCR assay that enables detection of bacterial DNA and then detection of the organisms was determined using genus and species specific PCR assays. This assay was evaluated using clinical specimens and was found to be quite sensitive and specific. Their PCR results matched with the conventional culture identifications. The conventional and SYBR green real time multiplex PCR assays takes only 3 h to be performed and has the potential to replace the conventional culture technique and thus can speed up the treatment process. This technique has the potential to be a valuable diagnostic tool for simultaneous identification of E. coli, K. pneumoniae, P. mirabilis, Citrobacter spp., E. cloacae and S. typhi. Â© 2010 Academic Journals.